2014
DOI: 10.1016/j.jnucmat.2014.07.071
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry effect on the irradiation response in the microstructure of zirconium carbides

Abstract: 2016-12-23T18:47:23

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…2 Similarly, variable carbon stoichiometry is exhibited by other TMCs, such as TiC x , [3][4][5] HfC x , 6,7 VC x , 8 NbC x , 3,9 TaC x , 10,11 and WC x . 12 Carbon stoichiometry affects the sinterability, [13][14][15] mechanical properties, 16,17 electrical properties, 18 and radiation resistance 19 of ZrC x ceramics. Short-and long-range ordering of carbon vacancies in nonstoichiometric carbides have both been studied theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…2 Similarly, variable carbon stoichiometry is exhibited by other TMCs, such as TiC x , [3][4][5] HfC x , 6,7 VC x , 8 NbC x , 3,9 TaC x , 10,11 and WC x . 12 Carbon stoichiometry affects the sinterability, [13][14][15] mechanical properties, 16,17 electrical properties, 18 and radiation resistance 19 of ZrC x ceramics. Short-and long-range ordering of carbon vacancies in nonstoichiometric carbides have both been studied theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…[11]. The Z contrast spherical aberration corrected STEM image of proton irradiated ZrC further confirms that those loops are interstitial type dislocation loops [20]. This indicates that the dislocation loops might be surrounded by C vacancies that have a much lower mobility as compared with C interstitials, however, there is no direct experimental evidence to confirm this yet.…”
Section: Methodsmentioning
confidence: 93%
“…Studies have indicated that the properties of ZrC vary with its stoichiometry (C/Zr atomic percentage ratio) [9]. For example Yang et al [25] indicated that the C/Zr ratio had a notable effect on the irradiation response of zone-refined ultra-high pure ZrC. They noted that the sub-stoichiometric ZrC samples (C/Zr<1) had an improved irradiation resistant microstructure compered to hyper-stoichiometric ZrC samples (C/Zr>1).…”
Section: Zrcmentioning
confidence: 99%